Determinants of Hospital Length of Stay Among Pulmonary Tuberculosis Inpatients at A Secondary General Hospital in Indonesia: A Comparative Analysis - Balqis Nurmauli Damanik; Hely Hely (Journal Medical Informatics Technology, 2026)
Tuberculosis (TB) remains a major public health challenge in Indonesia, which has the second-highest TB burden globally. Hospital length of stay (LOS) is an important indicator of inpatient care efficiency and influences reimbursement under the Indonesia Case-Based Groups (INA-CBGs) payment system. However, evidence regarding determinants of LOS in Indonesian secondary hospitals is still limited. This retrospective comparative study analyzed secondary medical-record data from a secondary general hospital in Medan, North Sumatra, collected between January and August 2025. Among 238 identified records, 215 patients with a primary diagnosis of pulmonary TB (ICD-10: A15.0–A16.9) met the inclusion criteria. LOS was calculated from admission and discharge dates. As LOS was not normally distributed (Shapiro–Wilk, p < 0.001), the Kruskal–Wallis and Mann–Whitney U tests with Dunn post-hoc correction were applied (α = 0.05). The median LOS was 3 days (IQR 2–4; range 0–13). Most patients were younger than 65 years (75.3%), while 51.2% had no documented comorbidity. Comorbidity burden was the only factor significantly associated with LOS (H = 18.74, p < 0.001; η² = 0.082). Patients with two or more comorbidities had significantly longer hospitalization than those without comorbidities (mean 4.18 vs. 2.82 days; p < 0.001) and those with one comorbidity (p = 0.013). No significant differences were found according to age group or insurance status. These findings indicate that comorbidity burden contributes to prolonged hospitalization among pulmonary TB inpatients and support integrating multimorbidity management into TB care. Larger multicenter prospective studies are needed to validate these findings.